Valorisation of recycled Construction and Demolition Wastes as backfill material for geosynthetic reinforced structures - Castorina S. Vieira (2015)
The reduction of non-renewable natural resources exploration has been a constant concern relating to the preservation of the environment that, simultaneously, encourages the use of alternative materials. Thus, over the last years the environmental sustainability has been demanding a progressive increase in the waste valorisation in construction. The valorisation of Construction and Demolition Wastes (CDW), on the one hand, reduces the use of natural resources (non-renewable) and, on the other hand, avoids congesting landfills with inert wastes coming from buildings and other constructions or infrastructures. Although some studies have been carried out on the application of recycled CDW, their valorisation in geosynthetic reinforced structures is almost an unexplored field. A research project aiming to contribute to the sustainable application of recycled CDW as backfill material in geosynthetic reinforced structures, is being developed at University of Porto, Portugal. This work presents and discusses some results of direct shear and pullout tests performed to characterise the behaviour of interfaces between recycled CDW and two geosynthetics (a geogrid and a high strength geotextile). The results have evidenced that CDW, properly selected and compacted, could exhibit shear strength similar to the natural materials commonly used in the construction of geosynthetic reinforced structures. The coefficients of interaction achieved for CDW/geosynthetic interfaces are in the range of this parameter for usual backfill materials, which corroborates the possible valorisation of recycled CDW as backfill material in geosynthetic reinforced structures.